Growth, yield and quality of high sugarcane (Saccharurn officinarum) genotypes as innuelaced due to planting seasons and fertility levels - SHUKLA, S K (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted for two consecutive cropping seasons during 200243 and 200344 at Lucknow, to evaluate 3 sugarcane (Saccharurn officinarrrrn) genotypes (’CoLk 941 1’, ’CoLk 9412’ and ’CoLk 94184’) under 3 N, P and K levels (150, 200, 250 kg N; 45, 60, 75 kg P and 45, 60, 75 kg Wha) to identify tillering behaviour, growth and sucrose accumulation of these genotypes under different planting seasons. Tiller number increased (149 500ha and 140 600lha in spring and sumer cane respectively) with the increase in the nutrient doses up to 200, SO and 60 kg NPK/ha. Planting seasons also influenced tillering pattern significantly (144 900ha in spring and 127 300ka in summer planted cane during September). Spring planted sugarcane gave significantly greater number of tillers compared to summer planted cane. ’CoLk 94184’ gave the highest number of tillers (197 800ha and 159 200/ha in spring and s u m e r planted cane respectively) as compared to ’CoEk 941 1’ and ’CoLk 9412’. Significantly higher cane yield (77.4 tonneslha) was harvested with genotype ’CoLk 94184’. It also had the higher pol percentage in juice (18.49) at 10-month stage in spring planted cane. Individual cane length (207.4 cm) and cane weight (693.8 g) in spring planted cane increased significantly up to 200,60 and 60 kg NPKha. Ratoon of the gemtype ’CoLk 94184’ gave highest number of millable canes (133 900/ha: and higher cane length (186.8 cm). Maximum ratoon yield (70.46 tonneska) and commercial cane sugar (9.39 tonneslha) were obtained with ’CoLk 94184’. Fertility level of 200,60, 60 kg NPWha was optimum for better growth, juice quality and cane yield during spring as well as summer planting in north Indian conditions.